Pemanfaatan Potensi di Desa Cibanteng untuk Integrasi Pertanian-Peternakan “Budidaya Jangkrik” - Verika Armansyah; Maria Tri Handayani (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Cibanteng Village is one of the 13 (thirteen) villages in the Ciampea District area with an area of 162,185 Ha, as of October 2018 the population of Cibanteng Village is 17,070 people, consisting of 8,700 men and 8,370 women. Potential in this Cibanteng village, namely tubers and cassava. This community service activity aims to exploit the potential of the village that is abundantly available and help the citizens in opening employment businesses. Cricket cultivation can help residents in minimizing feed costs and exploiting the potential of cassava leaf waste in Cibanteng Village. The method used is counseling. The activity was carried out in the Cibanteng Village Office Hall, Ciampea District. Participants numbered 14 people consisting of men and youth. The activity was carried out with two sessions, namely the delivery of material and discussion. Based on the results of the participant interviews, there has been an increase in specialization to perform cricket cultivation in the youth group or on the men. This community service activity from an economic perspective can increase community income and can open jobs for young people.